E-Module Based on Multicultural Values: Development Strategy for Islamic Primary Education - Azkiya, Hidayati; WS, Hasanuddin; Hayati, Yenni (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to explain the validity and practicality of the E-module theme 4 based on the values of multicultural education in Sub-theme 1 in the fourth grade of elementary school. The type of research used is research and development with a 4-D development model, namely define, design, development, and disseminate. The research instrument includes validation sheets by 3 expert lecturers, namely material experts, design experts, and linguists, and questionnaire responses from educators and students. Based on the results of the study, it was found that the assessment from material expert lecturers included aspects of content feasibility with a score (96,87%) in the very valid category and the integration aspect (92,85%) in the very valid category. The results of the assessment from design expert lecturers include the presentation component aspect (90,62%) in the very valid category, and the graphic aspect (82,14%) in the valid category. The assessment results from linguistic lecturers include aspects of language (92,5%) in the very valid category. From the three expert lecturers' assessment results, an overall average of 90,99% was obtained with a very valid category. The results of the practicality test by educators obtained an average of (91,67%) in the very practical category and the results of the practicality test by the students obtained an average of (97,99%) and categorized as very practical. From the results of the study, it can be concluded that the development of the e-module theme 4 based on the values of multicultural education in elementary schools is very valid, and very practical. So that it can be used in the learning process by educators, and for other researchers it is recommended to be able to develop e-learning modules based on character education values in other materials.